A Practitioner's Perspective on the Kenya I and Kenya II Cases Before the ICC: Interviews with the Lead Defense Counsel in the Ruto Case (Kenya I), Karim A.A. Khan, and Lead Prosecutor in the Kenyatta Case (Kenya II), Adesola Adeboyejo. Issue 79 (19th August 2014) - Mcgonigle Leyh, Brianne
On 10 September 2013 the International Criminal Court (ICC) began hearing a case against William Ruto, Deputy President of the Republic of Kenya, and Joshua Sang. The related case against the President of Kenya, Uhuru Muigai Kenyatta, was scheduled to begin in November 2013 but has since been postponed until October 2014. Both cases are noteworthy since they are the first against sitting politicians. Unsurprisingly, they have not been without controversy. These trials are challenging for the Court, not least because the Kenyan government recently passed a resolution withdrawing from the ICC and repealing its domestic legislation criminalizing international crimes, arguing that Kenya needed to restore it sovereignty and resist neo-colonialism. Although this withdrawal does not affect the current cases before the Court, it certainly makes cooperation with Kenya for the purpose of further investigations more difficult. Karim A.A. Khan, QC, formerly the defense counsel of Muthaura and currently the lead defense counsel of Ruto, raised these issues in an interview taking place one week before his opening statements in the Kenya I case. These same issues and concerns were also raised with Adesola Adeboyejo a lead prosecutor in the Kenya II case in December 2013.